UTILIZATION OF GEOGRAPHIC INFORMATION SYSTEMS IN IMPROVING SOCIAL RESILIENCE OF FARMER COMMUNITIES IN DEMAK - Permana, Dani Dasa; Legowo, Endro; Suwarno, Panji; Aris, Tomi (ITScience (Information Technology and Science), 2022)
Coastal abrasion that occurred in Demak Regency caused the loss of agricultural land due to drowning and brought social changes to the community among farmers. In anticipating this, it is necessary to overcome abrasion and increase the social resilience of the community. The ability of GIS in monitoring and mapping the area can be used as a means of useful information for the community. This study uses a quantitative approach. Data processing is carried out using satellite image data with different temporal, namely 1991, 2002, 2012, and 2021. Analysis of shoreline change predictions is carried out using the Digital Shoorelines Analysis System Method. The results of the analysis using the Digital Shoreline Analysis System (DSAS) method found that changes in the northern coastline of Demak Regency tend to experience significant abrasion from year to year. The coastline prediction obtained from the map is known to predict the coastline in the next 10 years the north coast of Demak Regency will experience abrasion. The highest abrasion occurred in Sayung District. Abrasion has an impact on changes in farmers' economic income which changes the behavior of the farming community so that efforts are needed to increase the resilience of the farming community, efforts that can be made include: 1). Prevention of coastal abrasion in areas that have the potential to experience coastal abrasion. 2). Building synergy to increase social resilience between the Government and the community. 3). Build and revive strategic leadership oriented to farmer welfare. The results of the research can also be used as material for consideration in policy making by the relevant government in disaster management efforts that may occur.